HISTORICAL PROCESS OF TURKISH LANGUAGE TEACHING AND SOME SUGGESTION ON TEACHING TURKISH TO FOREIGN STUDENTS - Hüseyin Kürşat TÜRKAN (Fırat University, 2019)
Language is not only a communication instrument of the society but also is regarded as an important representative which is liable for sustaining and spreading national culture of the society that belongs to. And yet, only objective in teaching Turkish as a foreign language that needs to be susceptible majorly must be comprehended not only teaching Turkish. If language is a holder of culture too, Turkish language as well as Turkish national culture should be suggested to people who aspire to learn Turkish. In globalising world, teaching language which has become crucial considerably recently and has been known that it has great market share should have professional comprehension and, as comprehension of being missionary of Europe, Turkish language should be counted as an opportunity and become across at this point. As so in every foreign language that is taught as a second language, main factor also in teaching Turkish as a foreign language is to gain basic learning outcome such as listening, reading, speaking and reading to students that have different cultures. The element of these abilities that are able to be gained, in other words, the goal of teaching Turkish should be stated that if it is resembled a bird, the wing of the bird belongs to pedagogues, other wing belongs to academicians who study about Turkish science. Especially, owing to these two disciplines coordinate with each other, Turkish which is taught as a second foreign language will retrieve more efficient and productive structure. Nowadays, even though Turkish is a native language / official language in many countries, it is noticed that there are not a lot of studies in teaching Turkish as a foreign language. In addition, teaching Turkish that has been only just perceived for our country is in service both in TOMER foundations of universities which belong to YOK (Council of Higher Education) and in councils in foreign countries which belong to Institution of Yunus Emre. The proposal will focus on the historical process of teaching Turkish and the suggestions related to Turkish teaching in TOMER units in Turkey.